Prevalence of Catatonic Schizophrenia Symptoms in a Psychiatric Hospital: A Retrospective Study - Javad Setare; Aram Karimian; Maryam Shoja; Fereshteh Bakhshian; Seyed Reza Saadatmehr (Iran University of Medical Sciences, 2018)
Background: Catatonia occurs as a complication of various medical and psychological illnesses that can be treated when diagnosed. Despite the high incidence of catatonia, the problem is poorly recognized. This study aimed at investigating the prevalence of catatonia and related factors in its diagnosis within a five year period in hospitalized patients of Zareh Psychiatric Center, Sari, Iran using computerized archive of records. Methods: It was a descriptive and retrospective study. The records of all patients with mental disorders admitted to Zareh Hospital between 2010 and 2014 were assessed. The data were collected using a demographic questionnaire and the Northoff Catatonia Scale (NCS). Then analyzed by statistical tests of multivariate logistic regression in SPSS-PC V. 20.  Results: Only 0.26% (26 per 10000 population) of patients had experienced catatonic schizophrenia during a five year period, including 42.11 men and 57.89 women. The prevalence of catatonic schizophrenia was significantly correlated with gender and age (P<0.05). Of the patients, 68.42% had a history of medication therapy and or hospitalization and 21.5% had a history of physical disorders. There was no significant relationship between the mean score of movement, emotional and behavioral changes with sex, education and age groups (P<0.05). Conclusion: Because many catatonic patients had a combination of medical and psychiatric problems, psychiatrists and psychiatric nurses are suggested to assess catatonia symptoms in both internal and psychiatric wards.